Boston keratoprosthesis for visual rehabilitation in porphyria cutanea tarda. (1st February 2013) - Sati, Alok; Sangwan, Virender S; Basu, Sayan; Kalaiselvan, Parthasarathi
Abstract : A 56-year-old man, presented with bilateral chronic visual loss associated with generalised skin lesions. He had undergone multiple penetrating keratoplasties in his right eye for recurrent corneal infections and perforations. On ocular examination, his left eye was phthisical and his right eye had light perception vision owing to a failed and vascularised corneal graft. Dermatological evaluation revealed multiple hyperpigmented and hypopigmented lesions along with thickening of skin on nose, scalp and dorsum of hands. Skin biopsy showed focal areas of deposition of faint periodic acid Schiff-positive diastase-resistant perivascular material. The high-performance liquid chromatography assessment revealed increased presence of porphyrins in blood and urine, thus confirming a diagnosis of porphyria cutanea tarda. The patient's vision in the right eye improved after undergoing Boston type 1 keratoprosthesis along with general photoprotective measures for the exposed parts of the body.